Improving antithrombotic management in patients with atrial fibrillation: current status and perspectives. - Levi, M; Hobbs, F; Jacobson, A; Pisters, R; Prisco, D; Bernardo, A; Haas, M; Heidrich, J; Rosenberg, M; Nielsen, J; Wuillemin, W (2009)
Despite overwhelming evidence of the benefits of risk-adjusted oral anticoagulation on stroke reduction in patients with atrial fibrillation (AF), there is still considerable undertreatment. A multidisciplinary expert group was formed to discuss issues surrounding anticoagulant treatment of patients with AF to try and achieve consensus on various aspects of the implementation of guidelines on oral anticoagulation therapy in AF. Panel members were cardiologists, hematologists, and laboratory and primary care physicians with specific expertise from Europe and the United States. One of the most important conclusions of the meeting was to enhance guideline adherence by better communication of the data showing that the benefits of stroke reduction outweigh the risk of bleeding associated with treatment with vitamin K antagonists. Management of oral anticoagulation therapy by dedicated centers, such as anticoagulation clinics, or by patient self-management may improve the quality of anticoagulation and facilitate the management of these patients and thereby further facilitate optimal antithrombotic management in patients with AF.